i)
"ysin2xdx-(1+y^2+cos^2x)dy=0\\\\\nP(x,y)=ysin2x, \\\\\nQ(x,y)=-(1+y^2+cos^2x)\\\\\n\\frac{\\partial P}{\\partial y}=sin2x\\\\\n\\frac{\\partial Q}{\\partial x}=-2cosx\\cdot (-sinx)=sin2x\\\\\n\\frac{\\partial P}{\\partial y}=\\frac{\\partial Q}{\\partial x}"
equation in total differentials
"\\exist u(x,y): \\frac{\\partial u}{\\partial x}=P(x,y)\\\\\n\\frac{\\partial u}{\\partial y}=Q(x,y)\\\\"
In our case
"\\frac{\\partial u}{\\partial x}=ysin2x\\\\\n\\frac{\\partial u}{\\partial y}=-(1+y^2+cos^2x)\\\\\nu(x,y)=\\int ysin2xdx=-\\frac{y}{2}cos2x+\\phi(y)"
Find
"\\frac{\\partial u}{\\partial y}=-\\frac{1}{2}cos2x+\\phi'(y)=\\\\\n=-\\frac{1}{2}(2cos^2x-1)+\\phi'(y)=\\frac{1}{2}-cos^2x+\\phi'(y)"
Then
"\\frac{1}{2}-cos^2x+\\phi'(y)=-1-y^2-cos^2x\\\\\n\\phi'(y)=-\\frac{3}{2}-y^2\\\\\n\\phi(y)=-\\frac{3}{2}y-\\frac{y^3}{3}\\\\\nu(x,y)=-\\frac{y}{2}cos2x-\\frac{3}{2}y-\\frac{y^3}{3}"
Answer: solution of equation is
"-\\frac{y}{2}cos2x-\\frac{3}{2}y-\\frac{y^3}{3}=C"
ii)
"(xy^2-x^2)dx+(3x^2y^2+x^2y-2x^3+y^2)dy=0\\\\\nP(x,y)=xy^2-x^2\\\\\nQ(x,y)=3x^2y^2+x^2y-2x^3+y^2\\\\\n\\frac{\\partial P}{\\partial y}=2xy\\\\\n\\frac{\\partial Q}{\\partial x}=6xy^2+2xy-6x^2\\\\\n\\frac{\\partial P}{\\partial y}\\neq\\frac{\\partial Q}{\\partial x}"
Find function "\\mu(y)"
"\\mu(y)=e^{\\int F(y)dy}"
where
"F(y)=\\frac{\\frac{\\partial P}{\\partial y}-\\frac{\\partial Q}{\\partial x}}{-P}=\\\\\n=\\frac{2xy-6xy^2-2xy+6x^2}{x^2-xy^2}=\\frac{6(x^2-xy^2)}{x^2-xy^2}=6\\\\\n\\mu(y)=e^{\\int6dy}=e^{6y}"
we multiply the equation by "e^{6y}"
"(xy^2-x^2)e^{6y}dx+\\\\\n+(3x^2y^2+x^2y-2x^3+y^2)e^{6y}dy=0\\\\\nP_1(x,y)=(xy^2-x^2)e^{6y}\\\\\nQ_1(x,y)=(3x^2y^2+x^2y-2x^3+y^2)e^{6y}\\\\\n\\frac{\\partial P_1}{\\partial y}=2xye^{6y}+6e^{6y}(xy^2-x^2)=\\\\\n=e^{6y}(2xy+6xy^2-6x^2)\\\\\n\\frac{\\partial Q_1}{\\partial x}=(6xy^2+2xy-6x^2)e^{6y}\\\\\n\\frac{\\partial P_1}{\\partial y}=\\frac{\\partial Q_1}{\\partial x}"
equation in total differentials
"\\exist u(x,y): \\frac{\\partial u}{\\partial x}=P_1(x,y)\\\\\n\\frac{\\partial u}{\\partial y}=Q_1(x,y)\\\\"
in our case
"\\frac{\\partial u}{\\partial x}=(xy^2-x^2)e^{6y}\\\\\n\\frac{\\partial u}{\\partial y}=(3x^2y^2+x^2y-2x^3+y^2)e^{6y}\\\\\nu=\\int((xy^2-x^2)e^{6y})dx=(\\frac{x^2y^2}{2}-\\frac{x^3}{3})e^{6y}+\\phi(y)"
Find
"\\frac{\\partial u}{\\partial y}=x^2ye^{6y}+(\\frac{x^2y^2}{2}-\\frac{x^3}{3})6e^{6y}+\\phi'(y)"
then
"x^2ye^{6y}+(\\frac{x^2y^2}{2}-\\frac{x^3}{3})6e^{6y}+\\phi'(y)=\\\\\n=(3x^2y^2+x^2y-2x^3+y^2)e^{6y}\\\\\n\\phi'(y)=y^2e^{6y}\\\\\n\\phi(y)=\\int y^2e^{6y}dy=\\frac{1}{6}\\int y^2de^{6y}=\\\\\n=\\frac{1}{6}(y^2e^{6y}-\\int 2ye^{6y}dy)=\\frac{1}{6}(y^2e^{6y}-\\frac{1}{3}\\int yde^{6y})=\\\\\n=\\frac{1}{6}(y^2e^{6y}-\\frac{1}{3}(ye^{6y}-\\int e^{6y}dy))=\\\\\n=\\frac{1}{6}y^2e^{6y}-\\frac{1}{18}ye^{6y}+\\frac{1}{108}e^{6y}"
"u=(\\frac{x^2y^2}{2}-\\frac{x^3}{3})e^{6y}+\\frac{1}{6}y^2e^{6y}-\\frac{1}{18}ye^{6y}+\\frac{1}{108}e^{6y}"
Answer: solution of equation is
"(\\frac{x^2y^2}{2}-\\frac{x^3}{3})e^{6y}+\\frac{1}{6}y^2e^{6y}-\\frac{1}{18}ye^{6y}+\\frac{1}{108}e^{6y}=c"
Comments
Leave a comment